The influence of substitution decisions made by national team coaches on final match outcomes at UEFA EURO 2024 - Gabrys, Tomasz; Chruscinski, Radoslaw; Garnys, Michal; Suva, Matej; Švátora, Karel (Frontiers in Sports and Active Living, 2025)
IntroductionCoaches leading national football teams during championship tournaments make decisions about tactical substitutions of players in critical match phases. This may be an attempt to change or defend a favorable score. This study focused on the time of decision-making of forced and planned substitutions, considering its characteristics: neutral, offensive, and defensive. The point of analysis of the substitutions was the match outcomes at the time of the substitutions and the final result and impact of the substitution concerning the result.MethodsA total of 51 matches played during the UEFA EURO 2024 football tournament were analyzed, during which 466 player substitutions were made. For the statistical analysis of the degree and strength of the relationship between the variables, the chi-square test, Cramer's V coefficient, and machine learning were used accordingly.Results72% of coaches’ decisions to player substitutions resulted from the decision to change the team's tactics by changing the team's setup or the players’ positions. The most common negative (69%) or positive (61%) impact occurred from the substitution of a player after the 20th minute.DiscussionThe decision trees used in the analysis determined the most advantageous time periods for coaches to make decisions about substitutions. The highest substitution effectiveness rate is obtained when the substitution is made between 60 and 85 min, and the lowest is made between 45 and 60 min.